Implementation of the Smart Village Policy to Enhance Public Services in Srimulyo Village, Piyungan Sub-district, Bantul Regency, Yogyakarta Special Region - Domi Sella; Sari Viciawati Machdum (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The Smart Village Policy is a program aimed at strengthening village governance and development (P3PD). It is designed to enhance village institutional capacity and improve governance to provide excellent services to the village community. Srimulyo Village has successfully implemented this policy and this study aims to describe its implementation in enhancing services. Edwards III's theory is used to observe the elements of communication, resources, disposition, and bureaucratic structure. This research is a qualitative descriptive study that examines village officials, facilitators, digital ambassadors, digital village cadres, and the management of the village digital community space as the subjects of analysis. Informants were selected using a "purposive sampling" technique. Data collection methods included observation, document studies, and interviews. The results indicate that effective communication, adequate resources, and the commitment of policy implementers have been crucial in providing services to the community in Srimulyo Village. It is observed that the bureaucratic structure parameter requires the Center for Competitiveness Development to develop an implementation SOP.